HYBRID JAVA PARALLELIZER: A FRAMEWORK FOR PARALLELIZATION OF JAVA CODE - Iqbal, A; Khan, M A (Pakistan journal of science, 2017)
[...]the programmer was still bound to provide directives to the compiler about possibly parallel portion of code and architectural specification in some predefined format. [...]these frameworks required source code as input, thereby constraining performance improvement subject to the availability of the source code. [...]many compilers, translators and libraries have been implemented to facilitate parallelization both in new languages and conventional languages like FORTRAN/C++ etc. The method name can't have a return type and could not be receiving arguments. [...]the inner classes were not supported. [...]no code dependencies were analyzed as each of iteration was supposed to contain independent work.